Identification of intracellular squalene in living algae, Aurantiochytrium mangrovei with hyper‐spectral coherent anti‐Stokes Raman microscopy using a sub‐nanosecond supercontinuum laser source. (5th July 2016) - Ishitsuka, Kei; Koide, Masahiro; Yoshida, Masaki; Segawa, Hiroki; Leproux, Philippe; Couderc, Vincent; Watanabe, Makoto M.; Kano, Hideaki
Abstract : We applied hyper‐spectral coherent anti‐Stokes Raman scattering imaging to intracellular lipid identification in living microalgae, Aurantiochytrium mangrovei 18W‐13a. Two different lipids, squalene and triacylglycerol, were found inside living cells with clear vibrational contrast. Based on the endogenous lipid band as a result of the cis CC stretch vibrational mode, squalene and triacylglycerol were clearly distinguished in different intracellular areas. In particular, squalene was detected solely in vacuoles as lipid particles, which was also supported by electron microscopy. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : Incubation‐time‐dependent hyper‐spectral coherent anti‐Stokes Raman scattering (CARS) imaging. Cells were sampled in 24, 48, 72, and 96 h later after starting the cultivation. Optical image (a), CARS at cis CC stretch vibrational mode of squalene (b), CARS at cis CC stretch vibrational mode of triacylglycerol (c), and second harmonic generation (d).